2017
DOI: 10.1371/journal.pone.0183142
|View full text |Cite
|
Sign up to set email alerts
|

Minimally-invasive glaucoma surgeries (MIGS) for open angle glaucoma: A systematic review and meta-analysis

Abstract: BackgroundMIGS have been developed as a surgical alternative for glaucomatous patients.PurposeTo analyze the change in intraocular pressure (IOP) and glaucoma medications using different MIGS devices (Trabectome, iStent, Excimer Laser Trabeculotomy (ELT), iStent Supra, CyPass, XEN, Hydrus, Fugo Blade, Ab interno canaloplasty, Goniscopy-assisted transluminal trabeculotomy) as a solo procedure or in association with phacoemulsification.MethodsRandomized control trials (RCT) and non-RCT (non randomized comparativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
322
1
8

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 356 publications
(340 citation statements)
references
References 59 publications
9
322
1
8
Order By: Relevance
“…The effect size reported by Hooshmand et al is smaller than reported separately for the phaco‐iStent or phaco‐iStent inject . This may reflect a “real‐world” setting compared to that of a clinical trial—for example, pre‐ and post‐operative drop washout periods were not included.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…The effect size reported by Hooshmand et al is smaller than reported separately for the phaco‐iStent or phaco‐iStent inject . This may reflect a “real‐world” setting compared to that of a clinical trial—for example, pre‐ and post‐operative drop washout periods were not included.…”
mentioning
confidence: 87%
“…The quality of evidence continues to improve, with a recent publication of meta‐analyses of the first‐generation iStent—both combined with phacoemulsification and as stand‐alone surgery—and a 2‐year prospective randomized control trial of the second‐generation iStent inject . The safety of these devices is well‐established in the short term—the most common adverse events are transient hyphema, stent malposition or blockage—and long‐term data are awaited.…”
mentioning
confidence: 99%
“…The introduction of microinvasive or minimally invasive glaucoma surgeries (MIGS) in the surgical management of open‐angle glaucoma in humans represents an innovative development. The impact of the various MIGS remains to be determined with long‐term outcomes of effective IOP reduction and complications, and with appropriate comparative effectiveness trials and meta‐analyses . Because of their minimal invasiveness with moderate IOP reductions, these aqueous humor draining techniques are being considered more often as alternatives for the treatment of early glaucoma stages, instead of medical therapies .…”
Section: Novel Surgical Therapies To Control Iopmentioning
confidence: 99%
“…Minimally invasive glaucoma surgery (MIGS) has recently been introduced and is becoming popular for controlling IOP in patients with glaucoma . MIGS results in IOP reduction via an ab interno or externo approach to facilitate aqueous outflow with minimizing adjacent tissue damage, and has a high safety profile and rapid recovery .…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Minimally invasive glaucoma surgery (MIGS) has recently been introduced and is becoming popular for controlling IOP in patients with glaucoma. [10][11][12] MIGS results in IOP reduction via an ab interno or externo approach to facilitate aqueous outflow with minimizing adjacent tissue damage, and has a high safety profile and rapid recovery. 11 MIGS involves specialized implants or devices, and can be performed simultaneously at the time of cataract surgery through a small corneal incision without damaging the conjunctiva.…”
Section: Introductionmentioning
confidence: 99%